Restorative justice: integrating theory, research, and practice - Hass-Wisecup, Aida Y. (Carolina Academic Press, 2018)
What is restorative justice? -- Historical and theoretical framework of restorative justice -- The pillars of restorative values -- Victim-offender mediation -- Family group conferencing -- Victim impact panels -- Circles -- Reparative boards -- Restorative justice : policing and courts